THE INFLUENCE OF TRANSPARENCY AND ACCOUNTABILITY LOCAL GOVERNMENT FINANCIAL REPORT ON THE LEVEL OF CORRUPTION LOCAL GOVERNMENT OF SUMATERA AREA - Khairudin KHAIRUDIN; Rosmiati ROSMIATI; Herry Goenawan Soedarsa; Rina Erlanda (International Conference On Law, Business and Governance (ICon-LBG), 2016)
Positive developments of government accountability a region characterized by the increases in WTP opinion for local governments it turns out that will be followed by the increases in of criminal acts of corruption conducted by the regional government officials. Corrupt practices is certainly preventable when applying transparency of local governments and accountability for financial management. This study attempts to prove empirically the influence of transparency and accountability local government financial report on the corruption local governments in Sumatera. Tests were conducted with 15 local governments in Sumatera. The data used are sourced from KPK, the website of the local government each, and from BPK RI 2011-2013 periode. This research used a linear regression multiple analysis. The result research showed that transparency it has positive effects and insignificant on the level corruption local government and accountability has positive effects and significant on the level corruption local government.